Fabrication of Platinum Nanowires via Electrodeposition of Platinum-Phenothiazine Complex in freshly prepared Anodic Aluminium Oxide Template - Ali Mahmmood, Waleed; Mohammed Ali Alsammarraie, Abdulkareem; Jabar Ahmed, Alya'a (Asian Journal of Chemistry, 2013)
Porous anodic aluminum oxide film with self-ordered character, has been widely used as the template for fabricating nano-structural materials. In this study, highly ordered anodic aluminum oxide template was fabricated in phosphoric acid by the two-step anodic oxidation process. The anodizing voltage was maintained at 60 V. The results showed that 20 % phosphoric acid and 5 ºC are suitable to prepare anodic aluminum oxide templates with a pore diameters of 130 nm. The fabricated anodic aluminum oxide films then subjected to post electrodepositing of Pt nanowires from freshly prepared Pt-phenothiazine complex, a forest of nanowires with a diameter nearly closed to the started anodic aluminum oxide pores sizes achieved. The morphology and surface structure of the anodic aluminum oxide films were examined before and after electrodepositing by; scanning electron microscopy, atomic force microscope and X-ray diffraction spectroscopy.